Changing trends in serotypes of S. pneumoniae isolates causing invasive and non-invasive diseases in unvaccinated population in Mexico (2000-2014). (May 2017) - ,; Márquez-Díaz, Francisco; Martínez-Medina, Lucila; Olvera-Herrera, María Elizabeth; Miranda-Novales, Maria Guadalupe; Camacho-Velázquez, Martha; Vásquez-Rosales, José Guillermo; Vázquez-Larios, Rosario; Rivera-Martínez, Eduardo; Hernández-Dueñas, Ana María; López-Martínez, Briceida; Moreno-Espinoza, Sarbelio; et al.
Highlights: We describe a decrease in the proportion of pneumococcal vaccine serotypes among people >5 years of age after introduction of PCV. The strongest decrease of pneumococcal diseases was observed in the group of adults from 18 to 49 years of age. A statistically significant increase of serotype 19A in all study groups was observed, except in adults ≥65 years. A significant increase was observed in serogroup 15 in the age group 50-64 years and serogroup 23 in children and adolescents among 5-17 years old. Abstract: Objective: Introduction of pneumococcal conjugate vaccines (PCV) targeted against a limited number of serotypes substantially decreased invasive (IPD) and non-invasive pneumococcal diseases (NIPD) but it was accompanied by non-vaccine type replacement disease. After 9 years of introduction of PCV in Mexico, we analyze the evidence of the indirect effects on IPD and NIPD serotype distribution among groups not targeted to receive the vaccine. Methods: From January 2000 to December 2014, pneumococcal strains isolated from IPD and NIPD cases from patients ≥5 years of age from participant hospitals of the SIREVA II (Sistema Regional de Vacunas) network were serotyped. A regression analysis was performed considering year and proportion of serotypes included in the different vaccine formulations (PCV7, PCV10 and PCV13). The slope was obtained for each regression line and their correspondent p-value. The proportion of each serotype in the pre-PCV7 and post-PCV7 periods was evaluated by χ2 test. Results: From a total of 1147 pneumococcal strains recovered, 570 corresponded to the pre-PCV7 and 577 to the post-PCV7 periods. The proportion of vaccine serotypes included in the three PCV formulations decreased by 2.4, 2.6 and 1.3%, respectively per year during the study period. A significant increase of serotype 19A was observed in the post-vaccine period in all age groups. Conclusions: A percentage of annual decline of serotypes causing IPD and NIPD included in PCV was detected among groups not targeted to receive the vaccine, probably due to herd effect. Considering pneumococcal serotype distribution is a dynamic process, we highlight the importance of surveillance programs.